Lin11-Isl1-Mec3 Domain Proteins as Mechanotransducers in Endothelial and Vascular Smooth Muscle Cells - Sporkova, Alexandra; Ghosh, Subhajit; Al-Hasani, Jaafar; Hecker, Markus (Frontiers in Physiology, 2021)
Arterial hypertension is the leading risk factor for cardiovascular morbidity and mortality worldwide. However, little is known about the cellular mechanisms underlying it. In small arteries and arterioles, a chronic increase in blood pressure raises wall tension, hence stretches namely the medial vascular smooth muscle cells (VSMC) but also endothelial cell (EC) to cell contacts. Initially compensated by an increase in vascular tone, the continuous biomechanical strain causes a prominent change in gene expression in both cell types, frequently driving an arterial inward remodelling process that ultimately results in a reduction in lumen diameter, stiffening of the vessel wall and fixation of blood pressure, namely diastolic blood pressure, at the elevated level. Sensing and propagation of this supraphysiological stretch into the nucleus of VSMC and EC therefore seems to be a crucial step in the initiation and advancement of hypertension-induced arterial remodelling. Focal adhesions (FA) represent an important interface between the extracellular matrix and Lin11-Isl1-Mec3 (LIM) domain-containing proteins, which can translocate from the FA into the nucleus where they affect gene expression. The varying biomechanical cues to which vascular cells are exposed can thus be rapidly and specifically propagated to the nucleus. Zyxin was the first protein described with such mechanotransducing properties. It comprises 3 C-terminal LIM domains, a leucine-rich nuclear export signal (NES), and N-terminal features that support its association with the actin cytoskeleton. In the cytoplasm, zyxin promotes actin assembly and organisation as well as cell motility. In EC, zyxin acts as a transcription factor whereas in VSMC it has a less direct effect on mechanosensitive gene expression. In terms of homology and structural features, lipoma preferred partner (LPP) is the nearest relative of zyxin among the LIM domain proteins. It is almost exclusively expressed by smooth muscle cells in the adult, resides like zyxin at FA but seems to affect mechanosensitive gene expression indirectly, possibly via altering cortical actin dynamics. Here we highlight what is currently known about the role of these LIM domain proteins in mechanosensing and transduction in vascular cells.